Diagnosing the Problem of Christian Immaturity: A Historical Perspective - Hindmarsh, D. Bruce (Journal of spiritual formation & soul care, 2025)
A historical perspective on the problem of Christian immaturity is found in classical writings on Christian spirituality across the centuries. Here we find that the Christian will fail to mature without a clear sense of the goal of the spiritual life. Spiritual maturity will be inhibited also by a two-tier spirituality that obscures the universal call to holiness, and by any teaching that allows Christians to settle too into a merely nominal faith. Classical spiritual texts had a profound sense of the depth of the intractable human predicament in sin that contrasts with the modern attitude, suggesting that maturity will be inhibited if we do not appreciate how deep the trouble goes. Lastly, we find that an anthropocentric focus in spirituality, appropriate as the spiritual life begins, is an obstacle to maturity if the Christian fails to move beyond this to an attitude of contemplation, focusing more solely upon Jesus Christ.